Diffusion processes with Gamma-distributed resetting and non-instantaneous returns. (7th June 2022) - Radice, Mattia
Abstract: We consider the dynamical evolution of a Brownian particle undergoing stochastic resetting, meaning that after random periods of time it is forced to return to the starting position. The intervals after which the random motion is stopped are drawn from a Gamma distribution of shape parameter α and scale parameter r, while the return motion is performed at constant velocity v, so that the time cost for a reset is correlated to the last position occupied during the stochastic phase. We show that for any value of α the process reaches a non-equilibrium steady state and unveil the dependence of the stationary distribution on v . Interestingly, there is a single value of α for which the steady state is unaffected by the return velocity. Furthermore, we consider the efficiency of the search process by computing explicitly the mean first passage time. All our findings are corroborated by numerical simulations.